2007
DOI: 10.1111/j.1600-0404.2006.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Almotriptan and zolmitriptan in the acute treatment of migraine

Abstract: Objective: To compare almotriptan and zolmitriptan in the treatment of acute migraine. Methods: This multicentre, double-blind trial randomized adult migraineurs to almotriptan 12.5 mg (n ¼ 532) or zolmitriptan 2.5 mg (n ¼ 530) for the treatment of a single migraine attack. The primary end point was sustained pain free plus no adverse events (SNAE); other end points included pain relief and pain free at several time points, sustained pain free, headache recurrence, use of rescue medication, functional impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…16 This is comparable to the 2-hour pain-relief rates of 65.4% and 70.2% and the 2-hour pain-free rates of 43.5% and 48.3% reported for almotriptan and zolmitriptan, respectively, in the primary analysis of all patients. 20 In agreement with these data, results of this current study have demonstrated that almotriptan is more effective than placebo in the acute treatment of migraine attacks, relief from migraine-associated symptoms, and providing a return to normal functioning in both MRM and nonMRM.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…16 This is comparable to the 2-hour pain-relief rates of 65.4% and 70.2% and the 2-hour pain-free rates of 43.5% and 48.3% reported for almotriptan and zolmitriptan, respectively, in the primary analysis of all patients. 20 In agreement with these data, results of this current study have demonstrated that almotriptan is more effective than placebo in the acute treatment of migraine attacks, relief from migraine-associated symptoms, and providing a return to normal functioning in both MRM and nonMRM.…”
Section: Discussionsupporting
confidence: 89%
“…16 The large (N = 1061) multicenter, multinational, randomized, double-blind, parallel-group clinical trial, conducted at 118 centers in 9 European countries, evaluated the efficacy and tolerability of almotriptan 12.5 mg vs zolmitriptan 2.5 mg in the acute treatment of migraine. 20 A retrospective analysis of this trial included 902 women, 255 of whom treated a menstrual migraine attack (136 with almotriptan and 119 with zolmitriptan). 16 No significant difference between the 2 treatments was found and these findings also did not appear to be different from the primary analysis which included all patients and all migraines.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this and to differences in individual responses, including adverse effects, the effects to a therapy may vary. [19][20][21][22][23][24] Therefore it has been suggested by McQuay and coauthors that we need new trial designs in order to capture the reality of the range of response in clinical practice. 3 They have suggested that this design should have the following properties:…”
Section: Clinical Acupuncture Trial Designsmentioning
confidence: 99%
“…Более того, авторы не выявили более значительного ограничения работоспособности при менструальной мигрени [2]. Мигрень одинаково хорошо ку-пируется с помощью немедикаментозного [11] и медикамен-тозного [14,30,[39][40][41] лечения в разные фазы менструально-го цикла. M. Diamond et al [28] выполнили ретроспективный анализ исследования AEGIS, проведенного в США в 2007 г. Авторы проанализировали все мигренозные атаки, зафикси-рованные у 190 пациенток, у которых за время исследования отмечалась хотя бы одна менструация.…”
unclassified